Data Journalism in Turkey: Developing a Scale and Measuring Journalists’ Skills - Seçil Özay; Serkan Bayrakcı (İnsan & Toplum)
Data journalism has recently emerged as an important method of news gathering and editing in journalism. For data journalism -which includes the process of producing news from data- journalists need to have various skills and competencies. As a result of the literature review, it is observed that the required skills and competencies for data journalism have not been determined precisely, and in this regard, there is a lack of quantitative studies to measure these skills and competencies of data journalism. This study aims to develop a unique scale that will reveal the data journalism skills of news producers. For this purpose, a data journalism scale has been developed through an online survey applied to news producers registered with the Turkish Press Agency (BIK). As a result of the item pool, expert views, and the scale application stages, it is understood that data journalism skills can be measured with a 2-factor structure: “data skills and tools” and “journalism skills.” The Cronbach Alpha reliability coefficient for the overall 21-item data journalism scale was calculated as 0.856, the data skills and tools factor as 0.883, and the journalism skill factor as 0.821. As a result of the research, it has been determined that while the journalism skills of the news producers are at a high level, their competence in data processing is low. In this sense -as a result of the study- a revision is recommended in both academic and professional training curriculum to include data collection, analysis and visualization skills that will improve data skills of news producers.